A MULTIMODAL ANALYSIS IN PANTENE ADVERTISEMENTS - Nadia Fadhilah Muslim, - (2020)
This study aims to investigate how Pantene Indonesian and International ads verbally and visually represent the image of women with beautiful strong hair and the ads' differences by means of Halliday's transitivity system (2014) and Kress and van Leeuwen's (2006) point of view. This study also focuses on what the differences signify. The study analyzes eight Pantene's advertisements, which consist of four Indonesian and International ads respectively. The data taken for this study are the Pantene Indonesian and International ads, focusing on the ads that show their brand ambassadors. The results of this study show that Pantene Indonesian ads describe women with strong hair as something that is coveted by women in Indonesia. Similarly, in Pantene International ads, the figure of a woman with strong and beautiful hair is described as a beautiful woman. In the Pantene Indonesian advertisement, it can be seen that ads makers use the implicit persuasive method, whereas in the International Pantene, the method is explicit declarative employed which can be seen by viewers directly. These differences verify the stereotypes attached to Indonesian and International market, namely being communal and individual, respectively.